Pomiędzy konwencją a kreacją językową. "Miasto" w "Podróży do Ziemi Świętej, Syrii i Egiptu" Mikołaja Krzysztofa Radziwiłła "Sierotki" = Between convention and linguistic creation. "A city" in the "Podróż do Ziemi Świętej, Syrii i Egiptu" by Mikołaj Krzysztof Radziwiłł "Sierotka" - Zarębski, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article tries to describe the linguistic creation of a city in the 16th century diary written by Mikołaj Krzysztof Radziwiłł. During his journey to Jerusalem Radziwiłł visited many exotic, for the Polish traveller, cities and towns to whom he devoted a lot of space in his diary.
Keywords: miasto; językowa kreacja; pamiętnik; Radziwiłł, Mikołaj Krzysztof (1549-1616); city; language creation; diary